Voices in the revolution: Resisting territorial stigma and social relegation in Porto's historic centre (1974–1976). Issue 4 (July 2018) - Queirós, João; Borges Pereira, Virgílio
This article tries to broaden the research agenda on territorial stigmatisation. It reviews some theoretical arguments on the relevance of a relational sociological reading of the processes of territorial stigmatisation, and proposes a study of these processes during a period of political revolution and social instability, through discussion of the case presented by the city of Porto, Portugal, in the mid-1970s. Based on the study of institutional archives, ethnographic work in several neighbourhoods, and semi-structured interviews with social actors involved in these processes, the article describes the urban and housing conditions of inner city Porto's working-class boroughs in the first three quarters of the 20th century and discusses the forms of political and social resistance taken up by residents from the most dilapidated neighbourhoods following the revolution of April 1974. The sociological analysis of the actions that gave origin to the voice of the residents in the historic centre of the city in this period reveals significant interaction with the processes of territorial stigmatisation, via organised collective resistance.